Evaluation of the effect of excipient content on the physical properties of Parkia speciosa Hassk. tablets through regression analysis - Bakaruddin, Faghira; Anuar, Mohd Shamsul; Mohd Nor, Mohd Zuhair (UiTM Press, Universiti Teknologi MARA, 2024)
Parkia speciosa Hassk. boasts numerous health benefits, yet its raw consumption may be inconvenient or unpalatable for many. To date, limited research has explored the development of Parkia speciosa Hassk. chewable tablets. This study uses regression analysis to analyse the impact of compaction pressure and excipient compositions on the physical characteristics of these tablets. Various compositions of microcrystalline cellulose (MCC, MicroceLac® 100, Lot No.: L103155221) excipient and dried Parkia speciosa Hassk. powder underwent direct compaction at four compaction pressures (22.61, 37.68, 52.75, and 67.82 MPa), with friability and tensile strength measured to assess breakage resistance. The regression analyses were performed using the built-in regression analysis tools available in Microsoft Excel (Version 16.73 (23051401)). Both compaction variables significantly influenced tablet mechanical strength (p-values ≤ 0.05). Higher pressure and increased MCC excipient reduced friability, enhancing breakage resistance. The 44.11% MCC excipient formulation, compacted at 67.82 MPa, demonstrated the lowest friability and high tensile strength. The friability and tensile strength models demonstrate a strong to good fit to the data, with an Rsquared value of 86.48% and 63.77%, respectively. The coefficients' findings confirm the hypothesis, indicating that increased excipient composition and compaction pressure decrease friability and enhance tensile strength. This study's findings and predictive model are useful for expedited development and optimization of Parkia speciosa Hassk tablet formulation.